Trends of Fatal Poisoning in Vadodara (Mid-Gujarat) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
Poisoning is one of the most common methods to commit suicide in India. Most of the population in India resides in rural areas, where pesticides are commonly used in farming, and that is why it is the most common poisoning in India. Vadodara is the ‘chemical city’ of Gujarat, because chemical factories are more here, and consequently the incidences of accidental and intentional poisoning are also higher at this centre. A detailed knowledge about the nature and magnitude of the poisoning cases in this particular area is significant for early diagnosis and prompt treatment. To know the trends of fatal poisoning in mid-Gujarat, we conducted a retrospective study in the Department of Forensic Medicine, S.S.G. Hospital and Medical College, Vadodara. A total of 289 cases of fatal poisoning were brought to us for post-mortem examination during the span of 1 year (from January to December 2008), and therefore all data related to age, sex and seasonal variation with manner of poisoning were studied with detailed autopsy examination. The results of chemical analysis of routine viscera were subsequently analysed after receiving forensic science laboratory reports. Our study revealed that the majority of victims were Hindus, males 21-30 years of age who died due to self-ingestion of insecticide poison in the initial months of the year.
Keywords: Poisoning; Suicide; Insecticide